PERSONALITAS ANGELA MERKEL DALAM UPAYA JERMAN MENGAKHIRI KRISIS LIBYA - Alifienna Amelia (Journal of International Relations, 2023)
Germany was one of the countries that actively pursued peace for Libya. The achievement of peace in Libya by Germany was carried out to overcome the surge in the number of refugees from the Middle East to Europe via the Mediterranean crossing. Angela Merkel's persistence in achieving peace in Libya was demonstrated by the holding of a series of peace processes known as the Berlin Process. This foreign policy cannot be separated from the influence of Angela Merkel as one of the policy-making units of the German government. Angela Merkel's role in ending the Libyan crisis is one of the next steps to rebuilding Libya. Commitments from external stakeholders influencing the conflict in Libya were successfully achieved at the Berlin Conference for Libya, a ceasefire agreement was reached, the Government of National Unity was confirmed, and the second Berlin Conference for Libya was held. Responding to this phenomenon, this study questions the role of Merkel's personality in Libya's peace efforts. In order to answer this question, the author uses a foreign policy analysis framework that identifies the relationship between the personality of the leader and the foreign policy taken. This study finds that Libya's peace efforts are a manifestation of Angela Merkel's dominant personality, namely the conciliator type and the participatory orientation.